Do We Practice What We Preach? Goal Setting for Ecological Restoration. Issue 3 (26th February 2013) - Hallett, Lauren M.; Diver, Sibyl; Eitzel, Melissa V.; Olson, Jessica J.; Ramage, Benjamin S.; Sardinas, Hillary; Statman‐Weil, Zoe; Suding, Katharine N.
Abstract Over the last decade, several research and opinion pieces have challenged the tenets of restoration ecology but a lack of centralized data has impeded assessment of how scientific developments relate to on‐the‐ground restoration. In response, the Society for Ecological Restoration (SER) launched the Global Restoration Network (GRN) to catalog worldwide restoration efforts. We reviewed over 200 GRN projects to identify the goals governing restoration and the frequency with which they are measured. We used the SER Primer on Ecological Restoration to frame our analysis, categorizing goals by SER's attributes of restored ecosystems. We developed additional attributes to characterize goals not encompassed by the SER‐defined attributes. Nearly all projects included goals related to ecosystem form, namely similarity to reference conditions and the presence of indigenous species, and these goals were frequently measured. Most projects included goals related to ecosystem function, and many highlighted interactions between abiotic and biotic factors by either modifying abiotic conditions to support focal species or manipulating species to achieve desired ecosystem functions. Few projects had goals related to ecosystem stability, whereas the majority of projects had goals related to social values. Although less frequently measured, social goals were described as important for long‐term project success. In conclusion, science and practice frequently aligned on goals related to ecosystem composition and function, but scientific guidelines on resilience and self‐sustainability appear insufficient to guide practice. In contrast, the common inclusion of goals for human well‐being indicates that, if intended to advise practice, restoration guidelines should give direction on social goals.